CHALLENGES, BENEFITS, AND INSTRUCTIONAL BEST PRACTICES OF BLENDED LEARNING: Tantangan, Manfaat, dan Praktik Instruksional Terbaik Blended Learning - Sitti Hadijah (Perspektif Pendidikan dan Keguruan, 2017)
In technology based era nowadays, blended learning appears as an option to run interactive andmeaningful learning atmosphere by combining virtual and traditional learning settings. There have beennumerous studies conducted regarding to the implementation of blended learning activities. Manyresearchers suggested that blended learning methods are effective in facilitating the process of effectiveonline learning. However, teachers and students may encounter some difficulties in adjusting blendedlearning due to their unfamiliarity of new learning system that require them to fully understand it. Inline with the application of the blended learning in teaching and learning contexts, this paper providesdescriptive qualitative research of the relevant literature that aimed to present three points in relation tochallenges, benefits, and instructional best practices of blended learning in teaching and learning. Thefindings indicate that the implementation of blended learning can be a challenge for teachers if they arenot supported by self-confidence, competence, and adequate accessibility to technology resources.However, blended learning instruction provides positive benefits for both teachers and students, such aspedagogy improvements and easy access to knowledge. Hence, some efforts need to be considered byteachers to have effective course design and provide active learning approaches in both face to face andvirtual learning environments.